Nella terra di mezzo: cinema e immigrazione in Italia, 1990-2010 - Vanoli, G (2015)
The thesis explores the representation of migration to Italy, through the study of a range of films selected for their thematic relevance as much as their aesthetic complexity. Beyond the scope of film analysis, it aims to add a contextualization of the social, political and cultural issues that connect migration and cinema, at the point where film studies and cultural studies converge.